Volume models for Sal (Shorea robusta Gaertn.) in far-western Terai of Nepal - Subedi, T. (Banko Janakari, 2018)
Sal (Shorea robusta Gaertn.) is one of the most important commercial tree species in Nepal and far-western Terai is renowned for its forest. This study was carried out in far-western Terai to develop volume models of Sal at tree level using destructive sampling. Out of 99 sample trees, 81 data were used to develop the models and 18 data for validation of the selected models. Over bark stem diameters were measured at an interval of 0.5 m in lowermost three sections, at an interval of 1 m for one section and at an interval of 2 m in upper part of the trunk from the ground level. Smalian’s formula was used to compute tree volume. Seven regression models were tested using DBH as a predictor variable. Cross validation of the independent data set was used to validate the selected models. The graphical analysis and fit statistics of the models were evaluated to select the best fit model. The selected model for total over bark stem volume is ln V = - 8.04674 + 2.26641 ln DBH with R2 of 92 % and standard error of 0.18. Similarly, the selected models for over bark volume up to 10 and 20 cm top diameter have R2 of 82.41% and 79.97% and standard errors of 0.35 and 0.42, respectively. The prediction error of the selected model was found to be less than 6%. Forest managers can use the recommended model in estimation of timber volume of Sal in a particular forest area of this region for effective forest management. Banko Janakari A Journal of Forestry Information for Nepal Vol. 27, No. 2, 2017, page: 3-11